Lastnosti aluminija Al 99,7 za izdelavo tub z udarnim brizganjem - Vasevska, Trajanka (Kovine zlitine tehnologije, 1997)
The producers of packaging transform aluminium to internally varnished collapsible tubes. The material for these products must have required characteristics during the production, the filling and discharging of packaging. The results of the investigation show how to eliminate some difficulties by means of adequate technological changes.
Keywords: aluminij; Aluminij Mostar; aluminum; embalaža; udarno brizganje; mehanske lastnosti; trdota; žarjenje; natezna trdnost; meja plastičnosti; raztezek